1999
DOI: 10.1038/sj.gt.3300817
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fas (CD95/APO-1) and Fas ligand in apoptosis induced by ganciclovir treatment of tumor cells transduced with herpes simplex virus thymidine kinase

Abstract: Transduction of cancer cells with herpes simplex virus thy-HSVtk-transduced tumor cells after the cell cycle arrest midine kinase gene (HSVtk) followed by prodrug gancicloand before apoptosis. Increased expression of FasL could vir (GCV) treatment has been shown to induce apoptosis. also be observed in vivo in HSVtk-transduced tumors In this study, four murine tumors including B16F10 melainduced to regress by GCV treatment. Enzyme measurenoma, NG4TL4 sarcoma, H6 hepatoma and 1MEA 7R.1 ments using specific subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…It has been reported that GCV induces apoptosis via caspase-8 activation in p53 pro®cient HSVtk-expressing neuroblastoma cells, due to p53-mediated translocation of the CD95 receptor from the cytosol to the membrane without a ecting the CD95 ligand (Beltinger et al, 1999). Involvement of FasR/ FasL pathway in GCV-induced apoptosis was also demonstrated in di erent tumor cell lines, all of which possessed functional p53 (Wei et al, 1999;Beltinger et al, 2000). Since in our cell system expression of FasR was unaltered and caspase-8 was initially activated but not further induced, we assume that Fas/caspase-8-driven apoptosis plays a minor role in GCV treated cells not expressing wild-type p53.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that GCV induces apoptosis via caspase-8 activation in p53 pro®cient HSVtk-expressing neuroblastoma cells, due to p53-mediated translocation of the CD95 receptor from the cytosol to the membrane without a ecting the CD95 ligand (Beltinger et al, 1999). Involvement of FasR/ FasL pathway in GCV-induced apoptosis was also demonstrated in di erent tumor cell lines, all of which possessed functional p53 (Wei et al, 1999;Beltinger et al, 2000). Since in our cell system expression of FasR was unaltered and caspase-8 was initially activated but not further induced, we assume that Fas/caspase-8-driven apoptosis plays a minor role in GCV treated cells not expressing wild-type p53.…”
Section: Discussionmentioning
confidence: 89%
“…13 Bystander Fas-mediated apoptosis may have relevance in other cancer gene therapy strategies. HSVtk/GCV, 14,15 HSVtk/GCV plus IL-12, 16 and p53 17 have been shown to activate the Fas-mediated apoptotic death pathway. However, it is important to note that these observations may be cell-line dependent because other reports indicate that p53 and HSVtk/GCV utilize non-Fas-mediated apoptotic death pathways as well.…”
Section: Discussionmentioning
confidence: 99%
“…6 This indicates that p53-mediated apoptosis may be significantly involved in the induction of HSV-tk/GCV-induced cell death. 23,40 However, it cannot be excluded that the HSV-tk/GCV system also induces to some extent nonapoptotic cell death in human HCC cells that has been previously described for rat hepatoma cells and murine melanoma cells 2,28 or by an irreversible G2-M arrest. 43 Because cellular p53 accumulation induces Fas-mediated apoptosis by transcriptional activation of the Fas gene 44 and by cell-surface trafficking of Fas, 45 we analyzed Fas expression on the cell surface of p53-positive HepG2 and p53-negative Hep3B cells, as well as the induction of FasL following treatment with HSV-tk/GCV and PNP/fludarabine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In some cell lines, signal transduction pathways such as the CD95/Fas system may be central to HSV-tk-mediated cell death. 23 In addition, HSV-tk-induced cell death may induce a potent antitumor immunity, which might further improve the efficiency of suicide gene-mediated gene therapy. [24][25][26][27] In this context, a recent study in murine cell lines demonstrated that the antitumor immunity induced by HSVtk/GCV was dependent on hsp70 up-regulation during cellular necrosis, whereas apoptotic cell death failed to induce im-munity.…”
mentioning
confidence: 99%